Dampak Pendidikan Agama terhadap Kesehatan Reproduksi pada MAN 1 Mataram Nusa Tenggara Barat - Ali Khudrin (Analisa: Journal of Social Science and Religion, 2010)
This research was conducted at MAN 1 Mataram. Focus of this studyis an impact of religious education toward health reproduction of students.The main objective of this research is, are there any difference impact of religious learning toward reproduction attitudes among students majoring IPA, IPS and language?  This study uses a qualitative approach. Data are analyzed using two way anova analysis. This research shows that students’ understanding of health reproduction  is good and very good.  The impactsof health reproduction attitude are, firstly there is a significant difference reproductionattitude between students of IPA, IPS And Language With significant value 0,024 < 0,05. Secondly, There is difference reproduction attitude between male and female students with significant value 0,000 < 0,05.  To cope with this result, it needs a specific handbook related to health reproduc-tion referred to Islamic teaching for students. Keywords : Impact, Health reproduction, religious education